Properties of wood plastic composite using Mahang Gajah (macaranga gigantea) with different filler loading / Fatihah Samsudin - Samsudin, Fatihah (2008)
The properties of wood plastic composite using Mahang Gajah (Macaranga gigantea) as filler mixed with polypropylene has been carried out. The objective of this study was to evaluated the effect of three differences mix line of the filler loading with polypropylene on mechanical and physical properties of WPC. The amounts of filler loading are 15, 25 and 40%. Two type mechanical properties, flexural and tensile strength and 2 physical tests WA and TS are carried out. The result show out the MOE and Tmoe are increasing according increase the wood filler. For MOR and tensile the result decreasing when increase the wood filler. For the elongation, increase the wood filler decrease the elongation. WA and TS are decrease according increasing the wood filler. The conclusion are Mahang Gajah (Macaranga gigantea) are suitable used as wood filler for WPC.